2001
DOI: 10.1104/pp.125.2.943
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of the Preprotein Translocase of the Outer Mitochondrial Membrane from Arabidopsis. Identification of Multiple Forms of TOM20

Abstract: The translocase of the outer mitochondrial membrane (TOM) complex is a preprotein translocase that mediates transport of nuclear-encoded mitochondrial proteins across the outer mitochondrial membrane. Here we report the purification of this protein complex from Arabidopsis. On blue-native gels the Arabidopsis TOM complex runs at 230 kD and can be dissected into subunits of 34, 23, 21, 8, 7, and 6 kD. The identity of four subunits could be determined by immunoblotting and/or direct protein sequencing. The 21-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
141
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 177 publications
(144 citation statements)
references
References 47 publications
1
141
0
2
Order By: Relevance
“…3C). Significant mitochondrial contamination of the Arabidopsis chloroplast preparation is also unlikely given that mitochondrial preparations from Arabidopsis green tissues are difficult (Werhahn et al, 2001) and mitochondria and chloroplasts are collected from 23% (v/v)/40% (v/v) and 50% (v/v)/70% (v/v) Percoll interfaces, respectively (Rensink et al, 1998;Werhahn et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…3C). Significant mitochondrial contamination of the Arabidopsis chloroplast preparation is also unlikely given that mitochondrial preparations from Arabidopsis green tissues are difficult (Werhahn et al, 2001) and mitochondria and chloroplasts are collected from 23% (v/v)/40% (v/v) and 50% (v/v)/70% (v/v) Percoll interfaces, respectively (Rensink et al, 1998;Werhahn et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…High magnification confocal laser-scanning microscopy (CLSM) revealed that the fluorescence pattern attributable to Cb5-D was actually toroidal in shape ( Figure 2I) and that these structures enclosed the spherical fluorescent structures attributable to endogenous E1b ( Figures 2J and 2K). Coexpression of Cb5-D and green fluorescent protein (GFP)-Tom22 (a fusion protein consisting of GFP and the Arabidopsis thaliana 22-kD subunit of the translocase of the outer mitochondrial membrane; Werhahn et al, 2001) resulted in colocalization of these proteins in the same torus structures ( Figures 2L to 2N), indicating that Cb5-D was localized specifically to the outer membrane of mitochondria. Additional CLSM experiments revealed that the reticular fluorescence patterns attributable to ERlocalized Cb5-A, -B, and -C did not colocalize with, nor enclose, the spherical fluorescent structures attributable to E1b in the mitochondrial matrix (data shown only for myc-Cb5-A; Figures 2O to 2Q).…”
Section: Cb5-a -B and -C Are Localized To Er Whereas Cb5-d Is Locamentioning
confidence: 99%
“…Isolation and Subfractionation of Mitochondria from ArabidopsisMitochondria from Arabidopsis were purified as outlined in Werhahn et al (18). Organelles were resuspended in resuspension buffer (0.4 M mannitol, 1 mM EGTA, 10 mM Tricine, 0.2 mM PMSF, pH 7.2) and either stored at Ϫ80°C or directly used for the generation of mitochondrial subfractions.…”
Section: Methodsmentioning
confidence: 99%